Formulation and Characterization of Paroxetine Hydrochloride Nasal Gel: An Innovative Approach - Danga, Neelima; Korni, Rama Devi; Laveti, Vasavi; Sai Sampath, Karakavalasa SVVS; Panda, Jagadeesh; Pinagadi, Pavan Kumar (International Journal of Pharmaceutical Investigation, 2025)
Background Serotonin Reuptake Inhibitors (SSRIs) like paroxetine are selective. It is used to treat several illnesses, such as premenstrual dysphoric disorder, post-traumatic stress disorder, obsessive-compulsive disorder, social anxiety disorder, severe depressive disorder and panic disorder. Intranasal medications travel straight to the brain through the olfactory and trigeminal nerves bypassing the blood-brain barrier. As a result, the drug's high concentration reaches the intended location with less systemic exposure and related adverse effects. Paroxetine hydrochloride is formulated as a nasal gel for the treatment of depression. Materials and Methods Paroxetine hydrochloride nasal gel was prepared using HPMC K100M, Guar gum and Carbopol 934. Both formulations were developed using the dispersion method. The prepared nasal gels were assessed for physical appearance, pH, viscosity and stability. Drug release from the formulations was determined using an in vitro diffusion experiment. Results and Discussion Both formulations showed satisfactory physical characteristics concerning color, clarity, texture and consistency. pH of the Formulations was 5.8 (F1) and 5.4 (F4) which is under the limits of pH of nasal mucosa i.e. 5.5-6.5 making it non-irritant to the nasal cavity. The viscosity of the formulations was found to be 250 cP (F1) and 215 cP (F4). The spreadability of both formulations showed satisfactory results. The percentage of drug diffused was 91.87% (F1) and 94.37% (F4) in 5 hr. Both formulations were found to be stable when subjected to freeze-thaw cycling. Conclusion Nasal gels prepared using HPMC K100M and Carbopol 934 are a suitable dosage form for administration of paroxetine hydrochloride.
Keywords: Blood-brain barrier; First pass metabolism; In vitro diffusion studies; Nasal gel; Paroxetine HCl